Arabic Language Learning Innovation Based on Technology Utilization - Betty Mauli Rosa Bustam; Kharisma Noor Latifatul Mahmudah; Kun Hidayat (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Teachers' low utilization of technology in learning Arabic has become a common phenomenon in the education area in Indonesia. The findings of researchers at different schools show the same happening, which is supported by similar studies in various regions of Indonesia. The minimal utilization of technology is undoubtedly out of step with this era and with the Ministry of Education and Culture of the Republic of Indonesia, which is socialized through the Independent Curriculum. However, the findings of these studies do not provide a remedy, namely how to persuade Arabic language teachers to adapt to technology. Therefore, this research aims to provide an example of making a learning video by utilizing an application that is easy to use and can be obtained for free through the website. This research uses the Multimedia Development Life Cycle (MDLC) method, which makes multimedia from the concept stage to distribution. The result of this research is an Arabic learning video about gender. This gender material was chosen randomly among a variety of other Arabic language materials. This is intended as an example and it is hoped that Arabic language teachers at any level of education can follow the example of making this learning video by changing the material according to the curriculum at the level they teach.